Manajemen Supervisi Pengajar di Pondok Pesantren: Kualitas Hafalan Al-Qur'an Santri di Tahfidz Al-Qur'an wa Tafaquh Fiddin Al-Amin Batam - Jamzuri; Akhmad Shunhaji; Ahmad Zain Sarnoto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This abstract aims to examine and analyze the implementation of teaching supervision management at the Tahfidz Al-Qur'an wa Tafaquh Fiddin Al Amin Batam Islamic Boarding School in maintaining the quality of students' memorization of the Qur'an. The quality of Qur'an memorization is an essential aspect in education at this Islamic boarding school, so an appropriate supervision management approach is needed to ensure the achievement of educational goals. This Islamic boarding school has a great responsibility in producing a generation of Muslims who are able to memorize and understand the Qur'an in depth. Therefore, the implementation of effective teaching supervision management is the main thing in ensuring the expected quality of education. This study uses a qualitative approach to explore the implementation of supervision management in the Islamic boarding school. Data was collected through participatory observation, in-depth interviews with Islamic boarding school managers, teachers, and students who are active in the Qur'an learning process, as well as analysis of documents related to teaching supervision. The results of the study revealed that effective supervision management in Islamic boarding schools includes several important stages. First, structured planning, including setting short-term and long-term goals, as well as learning strategies that are in accordance with the students' memorization targets. Second, the implementation of systematic supervision, including direct observation of the teaching process, evaluation of memorization quality, and providing feedback to teachers. Third, periodic evaluations to assess the effectiveness of the strategies implemented and ensure that there is an improvement in the achievement of student memorization. This research emphasizes the importance of developing a continuous and relevant supervision strategy in Islamic educational institutions. Good supervision management not only improves academic quality, but also strengthens the formation of students' character and morals in accordance with Islamic values. Supervision also contributes to the development of teachers' professionalism and supports the use of innovative learning methods in the teaching of the Qur'an.